Does the respondent’s role affect the final value of management effectiveness? The case of Brazilian marine protected areas - Brandão, Camila S.; da Rocha, Wesley; Zapelini, Cleverson; Teixeira, Jessyca L.; Schiavetti, Alexandre (Ethnobiology and Conservation, 2021)
Over the last decade, there has been a change in the way protected areas are managed across the world, as their management gradually ceases to be the sole responsibility of the government and is being shared with civil society. This study evaluates the management effectiveness, according to the managers and management boards of 20 marine protected areas (MPAs) on the coast of Brazil, using the Rapid Assessment and Prioritization of Protected Area Management (RAPPAM) methodology. There were differences in perspectives of the managers and management boards; 8 MPAs showed a significant difference in management effectiveness values, and 11 MPAs showed a change in management effectiveness category. In addition, there was a positive correlation between the year the management board was established, and the effectiveness value provided by the council, as well as a significant difference between the effectiveness values of the MPAs under federal and state responsibility. In view of these differences, it is suggested that evaluations of management effectiveness should be carried out not only with managers, but also with management boards to reduce possible incongruities caused by the responses of only one person.